ANALISIS KEMAMPUAN PSIKOMOTORIK SISWA PADA PRAKTIKUM KIMIA LAJU REAKSI - Fadhel, Muhammad; Fatisa, Yuni; Octarya, Zona (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
AbstractPractical work as a form of learning activity is also part of a series of learning processes. This research aimed at analyzing student psychomotor abilities in practical work on Reaction Rate lesson. This research was carried out in the Academic Year of 2023/2024 at State Islamic Senior High School 2 Kampar on Reaction Rate lesson. Quantitative descriptive method was used in this research. Purposive sampling was used in this research. The techniques of collecting data in this research were working assessment sheet, documentation, and interview to strengthen the data obtained. The results of data analysis showed that the mean score of student psychomotor abilities was 72.37% with good category. The highest mean score obtained was Creating indicator with the score 81.66% on good category, and the psychomotor ability with the lowest mean score was Manipulating indicator with the score 62.77% on good category. The psychomotor sub-indicator with the highest mean score was Returning the practical work equipment with the score 100% on very good category, and the psychomotor sub-indicator with the lowest mean score was Delivering the practical work results with the score 47.91% on sufficient category. Practical work learning could develop process skills, psychomotor skills, and scientific attitudes.Keywords: Psychomotor Abilities, Practical Work, Reaction Rate